Crucial determinants of adoption: material systems for banana and maize - Smale, Melinda; Kikulwe, Enoch; Edmeades, Svetlana; de Groote, Hugo; Byabachwezi, Mgenzi; Nkuba, Jackson (International Food Policy Research Institute, 2006)
Trait-based genetic change is broadly defined as the selection of traits for insertion and the choice of background planting material. For the technology to materialize, growers must perceive the yield advantages of the inserted traits. Field surveys confirm that farmers can readily discern stemborers and the losses they cause to maize crops (De Groote et al. 2004). In contrast, farmers have greater difficulty observing hidden biotic agents, such as nematode infestation of banana roots. This is further complicated by farmers incorrectly identifying the cause and effect of the pest or disease; for example, farmers often attribute the visible damages caused by Fusarium wilt, a soil-borne fungus, as well as nematodes, to weevils, and vice versa (Gold et al. 1993). Aware of these challenges, Uganda’s National Agricultural Research Organization has targeted more than one trait for insertion.